A novel NK-lysin in hybrid crucian carp can exhibit cytotoxic activity in fish cells and confer protection against Aeromonas hydrophila infection in comparison with Carassius cuvieri and Carassius auratus red var. Issue 116 (September 2021) - Luo, Sheng-Wei; Xiong, Ning-Xia; Luo, Zi-Ye; Fan, Lan-Fen; Luo, Kai-Kun; Mao, Zhuang-Wen; Liu, Shao-Jun; Wu, Chang; Hu, Fang-Zhou; Wang, Shi; Wen, Ming
Abstract: NK-lysin, an effector of natural killer (NK) cells and cytotoxic T lymphocytes (CTLs), not only exhibits cytotoxic effect in fish cells, but also participates in the immune defense against pathogenic infection. In this study, ORF sequences of RCC-NK-lysin, WCC-NK-lysin and WR-NK-lysin were 369 bp. Tissue-specific analysis revealed that the highest expressions of RCC-NK-lysin and WCC-NK-lysin were observed in gill, while the peaked level of WR-NK-lysin mRNA was observed in spleen. A. hydrophila infection sharply increased RCC-NK-lysin, WCC-NK-lysin and WR-NK-lysin mRNA expression in liver, trunk kidney and spleen. In addition, elevated levels of NK-lysin mRNA were observed in cultured fin cell lines of red crucian carp (RCC), white crucian carp (WCC) and their hybrid offspring (WR) after Lipopolysaccharide (LPS) challenge. RCC-NK-lysin, WCC-NK-lysin and WR-NK-lysin exerted regulatory roles in inducing ROS generation, modulating mitochondrial membrane potential, decreasing fish cell viability and antagonizing survival signalings, respectively. RCC/WCC/WR-NK-lysin-overexpressing fish could up-regulate expressions of inflammatory cytokines and decrease bacterial loads in spleen. These results indicated that NK-lysin in hybrid fish contained close sequence similarity to those of its parents, possessing the capacities of cytotoxicity and immune defense against bacterial infection. Highlights: Structure of NK-lysin in hybrid offspring was compared with those of its parents. Up-regulated expressions of RCC/WCC/WR-NK-lysin were observed following A. hydrophila challenge and LPS stimulation. RCC/WCC/WR-NK-lysin could cause the loss of MMP activity and decrease cell viability.